DOES THE COMBINATION OF ROSMARINUS OFFICINALIS AND CENTELLA ASIATICA NANOEMULSIONS AFFECT BDNF EXPRESSION IN THE GESTATIONAL DIABETES MELLITUS MODEL IN ZEBRAFISH LARVAE - Khotimah, Husnul; Lamadi, Sutini; Amelia, Rizki; Arista, Devi Maya; Prastiwi, Fajar Dwi; Raras, Tri Yudani Mardining (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Pancreatic β-cells compensate for the increased insulin demand due to increasing glucose levels during pregnancy or in gestational diabetes mellitus (GDM). The enzyme that regulates the rate of gluconeogenesis production is PEPCK. Circulatory and metabolic disturbances in the brain caused by hyperglycemia could affect brain-derived neurotrophic factor (BDNF) expression as an agent for neurodevelopment. Objective: The purpose of this work is to ascertain the impact of combining nanoemulsions of Rosmarinus officinalis and Centella asiatica on the expression of BDNF and PEPCK. Methods: This study was a true experimental laboratory using zebrafish larvae. The larvae were exposed to 3% glucose and a combination of nanoemulsion extracts. The study sample of zebrafish larvae at 72 hpf (hour post fertilization) was divided into control, glucose, treatment 1, 2, and 3, with the combination of Rosmarinus officinalis and Centella asiatica nanoemulsions at 2.5 μg/ml, 5 μg/ml, and 10 μg/ml, respectively. PEPCK and BDNF expression were measured by the real-time PCR method. Results: The expression of PEPCK increased significantly in the glucose group (3.05 ± 0.27). The combination of Rosmarinus officinalis and Centella asiatica nanoemulsions significantly decreased PEPCK (p-value 0,001 < 0.05). The BDNF level did not significantly differ (p-value 0.253 >0.05) among groups, but the highest level (1.06 ± 0.60) was gained in the T2 group, which received an embryonic medium (EM), 3% glucose, and the combination of Rosmarinus officinalis and Centella asiatica nanoemulsions at 5μg/ml. Conclusion: The combination of Rosmarinus officinalis and Centella asiatica nanoemulsions significantly reduces PEPCK expression but does not affect BDNF expression.